2016
DOI: 10.1073/pnas.1523698113
|View full text |Cite
|
Sign up to set email alerts
|

Brief intervention to encourage empathic discipline cuts suspension rates in half among adolescents

Abstract: Growing suspension rates predict major negative life outcomes, including adult incarceration and unemployment. Experiment 1 tested whether teachers (n = 39) could be encouraged to adopt an empathic rather than punitive mindset about discipline-to value students' perspectives and sustain positive relationships while encouraging better behavior. Experiment 2 tested whether an empathic response to misbehavior would sustain students' (n = 302) respect for teachers and motivation to behave well in class. These hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
263
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 311 publications
(288 citation statements)
references
References 24 publications
7
263
1
2
Order By: Relevance
“…Moreover, students only reported on relatively lower level disciplinary incidents—ones in which they were not removed from class. While trust is particularly relevant to how students interpret lower level and thus more ambiguous discipline (Okonofua, Paunesku, et al., ; Okonofua, Walton, et al., ), a crucial task for researchers is to examine if trust also buffers against more severe discipline (e.g., suspension from school).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, students only reported on relatively lower level disciplinary incidents—ones in which they were not removed from class. While trust is particularly relevant to how students interpret lower level and thus more ambiguous discipline (Okonofua, Paunesku, et al., ; Okonofua, Walton, et al., ), a crucial task for researchers is to examine if trust also buffers against more severe discipline (e.g., suspension from school).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the teacher level, teachers’ perspective‐taking of their students appears to matter for building trust. For example, one intervention found that when teachers were encouraged to assume an “empathic mindset” (i.e., to understand the students’ point of view when deciding how to respond to misconduct) as opposed to a control condition about student learning, suspension rates were reduced by 50% (Okonofua, Paunesku, et al., ; Okonofua, Walton, et al., ). The authors speculated that these effects were likely explained by increased trust in the student–teacher relationship.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations